Implementation of a PID-Based Temperature Control System on a Nextion HMI for Infant Warmer Applications - Ardiyanto, Farit; Slamet Pambudi; Joko Yunianto (JURNAL NASIONAL TEKNIK ELEKTRO, 2026)
Infant body temperature stability is paramount, especially for preterm newborns unable to maintain their own thermal equilibrium. Here, we explore a Proportional-Integral-Derivative (PID) control algorithm implemented directly on a Nextion Human–Machine Interface (HMI) to regulate infant warmer temperature. Unlike typical systems where the microcontroller holds the major PID calculation and the HMI acts as a display only, this method integrates the PID logic into the HMI itself, with possible reductions of microcontroller load, minimization of communication delays, and hardware architecture simplification. Three trials at a constant setpoint of 37 °C with varying combinations of PID gains were used with a fixed experimental setup. Temperature response indicators like rise time, settling time, percent overshoot, and steady-state error were measured and compared. Results indicate that with gains of Kp = 1.50, Ki = 0.05, and Kd = 1.50, the system reached a steady state of 36.97 °C with just 2.16 % of an overshoot and a settling time of about 7 minutes and satisfied neonatal warmer requirements. The results confirm that PID control executed directly on the Nextion HMI can achieve temperature regulation performance comparable to conventional microcontroller-based implementations while improving system simplicity and code efficiency. It presents a good alternative choice of low-power and portable infant warmer and also of other embedded hot and cold control systems.